Keep Up the Good Work! Age-Moderated Mediation Model on Intention to Retire - Dordoni, Paola; Van der Heijden, Beatrice; Peters, Pascale; Kraus-Hoogeveen, Sascha; Argentero, Piergiorgio (Frontiers in Psychology, 2017)
In European nations, the aging of the workforce is a major issue which is increasingly addressed both in national and organizational policies in order to sustain older workers' employability and to encourage longer working lives. Particularly older workers' employability can be viewed an important issue as this has the potential to motivate them for their work and change their intention to retire. Based on lifespan development theories and Van der Heijden's ‘employability enhancement model’, this paper develops and tests an age-moderated mediation model (which refers to the processes that we want to test in this model), linking older workers' (55 years old and over) perceptions of job support for learning (job-related factor) and perceptions of negative age stereotypes on productivity (organizational factor), on the one hand, and their intention to retire, on the other hand, via their participation in employability enhancing activities, being the mediator in our model. A total of 2,082 workers aged 55 years and above were included in the analyses. Results revealed that the two proposed relationships between the predictors and intention to retire were mediated by participation in employability enhancing activities, reflecting two mechanisms through which work context affects intention to retire (namely ‘a gain spiral and a loss spiral’). Multi-Group SEM analyses, distinguishing between two age groups (55–60 and 61–65 years old), revealed different paths for the two distinguished groups of older workers. Employability mediated the relationship between perceptions of job support for learning and intention to retire in both age groups, whereas it only mediated the relationship between perceptions of negative age stereotypes and intention to retire in the 55–60 group. From our empirical study, we may conclude that employability is an important factor in the light of older workers' intention to retire. In order to motivate this category of workers to participate in employability enhancing activities and to work longer, negative age stereotypes need to be combated. In addition, creating job support for learning over the lifespan is also an important HR practice to be implemented in nowadays' working life.